Analisis Perhitungan, Pencatatan, Penyetoran dan Pelaporan Pajak Penghasilan 21 Pada RS Vania Bogor Tahun 2015 - 2016 - Prihatono, Yudha Pratama; Sutomo, Hadi (Institut Bisnis dan Informatika Kesatuan, 2019)
This research was conducted at Vania Bogor Hospital which is located at Jalan Siliwangi No.42, Sukasari, Bogor Timur, Kota Bogor, West Java 16142. The purpose of this study was to find out the Suitability of Calculation, Deposit and Reporting at Vania Bogor Hospital in 2015-2016 by Regulation The Director of Tax as stated in PER 32 / PJ / 2015 and PER 16 / PJ / 2016 and Knowing the Suitability of Recordings conducted by Vania Bogor Hospital with generally accepted Accounting Standards. This research is a qualitative research with a descriptive approach. This method is used with the aim to answer and provide an overview of the analysis of calculation, recording, depositing and reporting PPh Article 21. The analysis method used by the writer is descriptive qualitative writing, which is an attempt to collect and compile a data, then analyze the data . Descriptive analysis is the data collected is in the form of numbers. The results of the research show that the calculation, recording, depositing and reporting conducted by Vania Bogor Hospital is in accordance with the generally accepted tax regulations and accounting standards. However, there are some SPT for Correction Periods in Reporting that were carried out by Vania Bogor Hospital which was caused by being wrong in calculating the number of employees. For Vania Bogor Hospital employees who are responsible for Article 21 PPh, it is advisable to do the right calculation between the number of employees who are still working and the number of employees who are no longer working at Vania Bogor Hospital.